Is something wrong with the second pillar in Switzerland?: Gender inequalities from a perspective of two Private Occupational Pension Institutions - Kucera, Jacqueline (My University, 2015)
Inequalities and old age pension systems have been analyzed in depth by many scholars. This study tackles the question of gender inequalities in a propaedeutic manner and asks: “Is something wrong with the second pillar in Switzerland?” By perceiving the occupational pension system as secure and safe, the focus of this thesis lies in the idea of guaranteeing equality for future pensions. The thesis asks whether gender inequalities occur through the mechanism of interpretation of the Federal Law of occupational pension schemes (LPP). In addition to that, the paper discusses the impact of the labor market on pension inequality. The focus lies on the analysis of gender inequalities at an institutional level, affecting retirees and employees of private occupational pension institutions in Switzerland. The thesis investigates how two specific pension institutions have designed their regulations in the context of legislative freedom, investigating whether the LPP is part of the problem causing gender inequalities between old age provisions. By using a mixed methods approach, the study demonstrates how two pension institutions are reproducing and enhancing employment and labor market inequalities at the intersection of the labour market, the occupational pension law, institutional regulations and organizational structures. The empirical findings in this thesis confirm the hypotheses that each occupational pension institution potentially enhances or reduces income inequalities at the institutional level. The type of pension fund may reinforce or reduce (pre-) existing (gender) inequalities within or between pension schemes by incorporating their own norms in their pension regulations, hereby offering better conditions than legally defined. The study illustrates that, independent on the labor market mechanisms, the affiliation of an employee to a specific type of pension institution is most important as the pension regulations are strongly determinant for the level of second pillar benefits. Thus, the thesis shows that pension fund regulations are of crucial importance. The thesis provides insight into the functioning of and the mechanisms within the LPP. It offers a roadmap with issues that people involved in the occupational pension system may bear in mind when they (re-) design the second pillar pension system.
Thèse de doctorat : Université de Neuchâtel, 2015
Keywords: inégalités entre hommes et femmes; institution de prévoyance; système suisse depension; écart de rente femmes/hommes; écart de salaire femmes/hommes; Etat providence en Suisse; lieu de travail suisse; marché suisse du travail; inégalités institutionnelles; rente vieillesse; inégalités entre les rentes; retraite; politique sociale; gender inequalities; occupational pension institutions; swiss pension system; gender pension gap; swiss welfare state; workplace in Switzerland; swiss labour market; institutional inequalities; old-age pension income; pension inequalities; retirement; social policy